Alma : Head to Toe = Alma : De Pies a Cabeza - Martinez-Neal, Juana (Somerville, Massachusetts : Candlewick Press, 2023)
Publisher Annotation: Get to know Alma, head to toe . . . in two languages! The beloved star of the Caldecott Honor Book Alma and How She Got Her Name appears in a series of joy-filled bilingual board books featuring words and simple phrases in English and Spanish. Juana Martinez- Neals bilingual board book teaches body parts while sharing moments in a little girls world, in a conversational narration (shown in both languages on every spread) combined with gentle, inviting illustrations.
In English and Spanish.
Keywords: Human body -- Juvenile fiction; Birds -- Juvenile fiction; Human body -- Fiction; Birds -- Fiction; Spanish language materials -- Bilingual; Board books